Who Works for Whom? Worker Sorting in a Model of Entrepreneurship with Heterogeneous Labor Markets - Emin Dinlersoz; Henry R. Hyatt; Hubert P. Janicki (Institute for the Study of Labor (IZA), 2016)
Young and small firms are typically matched with younger and nonemployed individuals, and they provide these workers with lower earnings compared to other firms. To explore the mechanisms behind these facts, a dynamic model of entrepreneurship is introduced, where individuals can choose not to work, become entrepreneurs, or work in one of the two sectors: corporate or entrepreneurial. The differences in production technology, financial constraints, and labor market frictions lead to sector-specific wages and worker sorting across the two sectors. Individuals with lower assets tend to accept lower-paying jobs in the entrepreneurial sector, an implication that finds support in the data. The effect on the entrepreneurial sector of changes in key parameters is also studied to explore some channels that may have contributed to the decline of entrepreneurship in the United States.
Keywords: L26; J21; J22; J23; J24; J30; E21; E23; E24; 330; entrepreneurship; borrowing constraints; financial frictions; labor market frictions; worker sorting; decline in entrepreneurship